Comparative Study of Heavy Metal Uptake by Invasive Plant in Two Aquatic Environment - HAMDI, HURULAIN SILMINA; Pa'ee, Furzani; Haiqal Hazwan Mohd Hanafi; Muhammad Amirullah Mohd Rosli (Enhanced Knowledge in Sciences and Technology, 2026)
Water pollution resulting from agricultural runoff and urban activities has become a major environmental concern due to its adverse effects on surface water quality and aquatic ecosystems. Conventional water treatment methods are often costly and require intensive maintenance, highlighting the need for sustainable and nature-based alternatives. Phytofiltration using aquatic macrophytes offers a low-cost and environmentally friendly approach for improving water quality. This study investigates the phytofiltration potential of water lily (Nymphaea spp.) and water hyacinth (Eichhornia crassipes) in two different freshwater systems, namely Tasik Laguna at Universiti Tun Hussein Onn Malaysia (UTHM) and the Sawah Ring irrigation canal. A three-week experimental study was conducted with three trials per week for each plant and water system combination. Water quality parameters including aluminium (Al), nitrite (NO₂⁻), nitrate (NO₃⁻), ammonia (NH₃/NH₄⁺), total hardness (THH), chloride (Cl⁻), phosphate (PO₄³⁻), copper (Cu), chlorophyll (CH) and pH were analyzed before and after each treatment period to evaluate pollutant removal efficiency. The average weekly percentage removal was calculated to compare the phytofiltration performance of both aquatic plants under different hydrological conditions. The results showed that water hyacinth exhibited exceeding 60% removal efficiency for nutrients and selected heavy metals in the Sawah Ring canal, which is characterised by flowing water and higher pollutant loads. In contrast, water lily demonstrated more consistent performance in the relatively stagnant lake environment of Tasik Laguna, contributing to nutrient reduction and chlorophyll control through sediment interaction and surface shading. In conclusion, this study demonstrates that aquatic plant-based phytfiltraton is an effective and sustainable method for improving surface water quality. The findings emphasize the importance of selecting appropriate plant species based on site specific conditions and support the application of nature-based solutions in water quality management.